The joy of music - Bernstein, Leonard, 1918-1990 (New York : Simon and Schuster, 1959)
Illustrated talks on music appreciation, based on the author's "Omnibus" television shows. Includes expanded scripts of seven of the shows
Introduction : the happy medium -- Imaginary conversations. Bull session in the Rockies ; Whatever happened to that great American symphony? ; Why don't you run upstairs and write a nice Gershwin tune? -- Interlude : Upper Dubbing, Calif. -- Photograph section -- Seven Omnibus television scripts. Beethoven's Fifth symphony ; The world of jazz ; The art of conducting ; American musical comedy ; Introduction to modern music ; The music of Johann Sebastian Bach ; What makes opera grand?
Keywords: Music -- History and criticism